2017
DOI: 10.1111/cns.12764
|View full text |Cite
|
Sign up to set email alerts
|

Claudin‐5 regulates blood‐brain barrier permeability by modifying brain microvascular endothelial cell proliferation, migration, and adhesion to prevent lung cancer metastasis

Abstract: CLDN5 regulates the permeability of BBB by regulating the proliferation, migration, and permeability of hCMEC/D3 cells, especially through the cell adhesion molecule signaling pathway, to enhance the function of the tight junctions, which was involved in reducing the formation of lung cancer brain metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 40 publications
1
65
0
Order By: Relevance
“…Recently, it was shown that the overexpression of claudin-5 in hCMEC/ D3 cells led to a reduction in the permeation of A549 cancer cells by approximately two-thirds, but did not lead to a noticeable improvement in electrical impedance. This suggested that additional mechanisms were missing to functionally incorporate claudin-5 at the tight junctions in the cell membrane [27]. Single cell RNA-seq data of mouse brain derived cells from the Betsholtz group [46] showed that fibroblast-like cells and not brain capillary endothelial cells expressed claudin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that the overexpression of claudin-5 in hCMEC/ D3 cells led to a reduction in the permeation of A549 cancer cells by approximately two-thirds, but did not lead to a noticeable improvement in electrical impedance. This suggested that additional mechanisms were missing to functionally incorporate claudin-5 at the tight junctions in the cell membrane [27]. Single cell RNA-seq data of mouse brain derived cells from the Betsholtz group [46] showed that fibroblast-like cells and not brain capillary endothelial cells expressed claudin-1.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the ABC transporters the highest abundant was ABCC1 (478) followed by ABCC4 (299), ABCB1 (106), ABCC3 (93), ABCC5 (92), ABCG2 (29) and ABCC2 (9). Quite high and moderate expression was found for JAM3 (320), ZO-1 (315), CDH5 (294) and Occludin (145), whereas low expression was found for Tricellulin (27) and JAM-2 (0.23).…”
Section: Human Brain Endothelial Hcmec/d3 Cells Express Several Tightmentioning
confidence: 99%
“…Jia reported that down-regulating CLDN5 increased tumor invasion and potential metastatic abilities [32]. Ma discovered CLDN5 was closely related to brain metastases from lung cancer [33]. In 2019, Jia indicated that high-dose bevacizumab likely increased lung tumor invasion and potential metastatic abilities through down-regulating CLDN5 [34].Moreover, CLDN5 showed a close relationship with mental illness, such as depression [35], schizophrenia [36], brain edema following fatal heat stroke [37] and tumor brain metastasis [38].…”
Section: Discussionmentioning
confidence: 99%
“…Cell viability was evaluated via cell proliferation assay kit as described in the specifications (WI, USA). For gene knockdown, negative control small interfering RNA (siRNA) (5′-UUCUCCGA ACGUGUCACGUTT-3′) and Tau siRNA (5′-CCGCCAGG AGUUCGAAGUGAU-3′), Claudin-1 siRNA (5′-GCAUG GUAUGGCAAUAGAA-3′), Claudin-5 siRNA (5′-CCAAC AUUGUCGUCCGCGATT-3′), Claudin-7 siRNA (5′-AUUA GGGCUCGAGUGGCCUGCAAGG-3′), and α-tubulin siRNA (5′-AGAUGUCAAUGCUGCCAUU-3′) sequences were designed in reference to the literatures [37][38][39][40][41] . Cells were plated in six-well plates at a density of 1 × 10 6 per well and cultured for 24 h; the medium was replaced with fresh medium containing 10% FBS when cells reach~70% confluency.…”
Section: Cell Culture Viability Assay and Transfectionmentioning
confidence: 99%